Use of arithmetic progression of the pearson correlation coefficient for prediction of surface distortion of ornamental rocks - Bolonini, Thiago M.; Godoy, Antonio M. [UNESP]; Figueiredo, Carlos Alberto M.; Maurício, António; Pereira, Manuel F. (UNESP - Universidade Estadual Paulista, 2019)
In accelerated aging of dimension stones in SO2 saturated chamber, the physico-chemical interactions has the purpose of simulate its exposure to acid rain. The presence of SO2, H2O, added to incident solar radiation (external) allow the photochemical formation of sulfuric acid (H2SO4) and the correlation between scanned surfaces of the specimens, before and after the exposure to H2SO4, provides the analysis of the alterations evolution. The estimated time spent, in years, for the changes to promote overall aesthetic distortion of the sample surface appearance is done through the arithmetic progression of the Pearson’s linear correlation coefficient (r) allowing, when equal to 0 (zero), assert the lack of correlation between images of samples subjected to the test and your original images. The results indicate the Butterfly Gold as the most susceptible to superficial aesthetic decharacterization (3,08 years), followed by the Butterfly Green (3,91 years) and Butterfly Beige (16,03 years). We emphasize that the decharacterization not necessarily imply in structural or physical-mechanical impairment. The concentration of the gas in the chamber (25 ppm) was intentionally elevated to accelerate the deterioration process. Remember that the camera simulates weather conditions practically in continuous flow requiring the researcher to the interpretations consider the SO2 concentration at the atmosphere, the duration of the rainy seasons, the incidence of acid rain and its intensity over a year in different territories. The estimates calculated do not prevent the application of these materials as external or internal coatings as usual cleaning procedures can be seamlessly applied to conservation.
Utilização da progressão aritmética do coeficiente de correlação de pearson para previsão da descaracterização superficial de rochas ornamentais
Keywords: Accelerated aging; Aesthetic decharacterization; Arithmetic progression; Correlation of images; Pearson’s linear correlation coefficient